Repeated Abutment Screw Fracture during Implant-Supported Prosthesis Fabrication Due to Internal Fixture Defect: A Case Report and Management Strategy - Soleimani, Soraya; Nikparto, Nariman; Eftekhar Ashtiani, Reza (Journal of Dental School, 2025)
Objectives: Dental implants have a high success rate for patients without teeth. However, complications can occur, particularly those related to mechanical issues such as abutment screw fractures. This case report presents an unusual incident of repeated abutment screw fracture during the impression and prosthesis fabrication stages which can be considered the first reported case of screw fracture during the prosthetic fabrication, while it usually presents years after delivery. Case: A 65-year-old female patient presented with repeated fractures of the abutment screws during prosthetics procedures. The initial tightening of the abutment to 32 N caused the fracture, and subsequent analysis revealed defects in the internal surface of the patient’s fixture that correlated with the abutment screw fractures. In a conservative management approach, transitioning to a lower torque abutment setting (20 N) was successful without complications. Conclusion: This case highlighted the critical importance of examining the internal structure of dental implants during complication management. The implant’s internal surface defects indicate a potential relationship between incorrect insertion torque and mechanical failures.